2018
DOI: 10.25081/jsa.2018.v2.919
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of vitamin-mineral premix by Spirulina and its effect on the performance of broiler

Abstract: The main purpose of this study was to explore the effects of Spirulina (Spirulina platensis) as a feed supplement by replacing Vitamin-Mineral Premix on the performance of broiler. The study explored that final body weight was 1039, 1070, 1044, 1065, 1117 and 893 g/bird in group 1, 2, 3, 4, 5 and 6 where significantly (p<0.5) higher weight observed in Spirulina group (5) but lower in negative control group (6). Feed intake observed more or less similar in all groups (1483±24g; p>0.5). Feed conversion ratio (kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…This however suggests the potential of higher levels of inclusion from 0.1% to 0.3% as a good source for partial or whole replacement of commercial vitamin-mineral premix. The results obtained from this study was however in agreement with the findings of Moury et al (2018) who concluded that the diets containing no vitamin-mineral premix with 100% Spirulina improved the performance of broiler chickens.…”
Section: Discussionsupporting
confidence: 92%
“…This however suggests the potential of higher levels of inclusion from 0.1% to 0.3% as a good source for partial or whole replacement of commercial vitamin-mineral premix. The results obtained from this study was however in agreement with the findings of Moury et al (2018) who concluded that the diets containing no vitamin-mineral premix with 100% Spirulina improved the performance of broiler chickens.…”
Section: Discussionsupporting
confidence: 92%
“…(3) SP supplements provide goats with a premix of vitamins and minerals that are not often available in conventional diets. As reported by Moury et al [ 33 ], vitamin supplementation is often not necessary when SP is added to animals’ diet. Adding a vitamins and minerals premix to an animals’ diet may affect their performance and carcass quality [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most common species of algae used in poultry nutrition are chlorella and Spirulina. It was reported by Moury et al [45] that supplementation of Spirulina platensis in broiler diets may completely replace the incorporation of vitamin-mineral premix. Moreover, it can be substitute the antibiotic usage in animals [46].…”
Section: Algaementioning
confidence: 99%